2013
DOI: 10.1287/deca.2013.0279
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Coherence Weighting for Optimizing Expert Forecasts

Abstract: Methods for eliciting and aggregating expert judgment are necessary when decision-relevant data are scarce. Such methods have been used for aggregating the judgments of a large, heterogeneous group of forecasters, as well as the multiple judgments produced from an individual forecaster. This paper addresses how multiple related individual forecasts can be used to improve aggregation of probabilities for a binary event across a set of forecasters. We extend previous efforts that use probabilistic incoherence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(114 citation statements)
references
References 38 publications
1
111
2
Order By: Relevance
“…In laboratory studies, Karvetski et al (75) showed that by eliciting extra judgments to determine how coherent a judgment is, adjusting the resulting set of judgments to make them more coherent, and then weighting those adjusted judgment on the basis of original coherence, a significant improvement in performance could be achieved.…”
Section: Combining Expert Judgmentsmentioning
confidence: 99%
“…In laboratory studies, Karvetski et al (75) showed that by eliciting extra judgments to determine how coherent a judgment is, adjusting the resulting set of judgments to make them more coherent, and then weighting those adjusted judgment on the basis of original coherence, a significant improvement in performance could be achieved.…”
Section: Combining Expert Judgmentsmentioning
confidence: 99%
“…Using machine learning techniques, Ghose et al (2012) proposed a random coefficient hybrid structural model for hotel ranking considering user behavior on social media and search engines. Based on two experiments over a crowdsourcing platform, a study by Karvetski et al (2013) argued that multiple related individual forecasts can be useful to improve aggregation of probabilities.…”
Section: Weeks and Veltri (2013)mentioning
confidence: 99%
“…Karvetski et al (2013) Data from two events Establish a model that can be used to remedy that occurs when forecasters use the probability that represents epistemic uncertainty. Leimeister et al (2009) 32 samples from an online survey on a platform Find optimal incentive and motivation for an online idea competition.…”
Section: Crooks Andmentioning
confidence: 99%
“…In this case, an inconsistency measure helps one to detect if a change approximates consistency or not. In other areas, inconsistency measures for probabilistic logic have found applications in merging conflicting opinions, leading to an increased predictive power [47,25], and in quantifying the incoherence of procedures from classical statistical hypothesis testing [41]. Example 1.1.…”
Section: Introductionmentioning
confidence: 99%